Multi-omics analyses on the response mechanisms of 'Shine Muscat' grapevine to low degree of excess copper stress (Low-ECS). (1st October 2021) - Chen, Mengxia; Fang, Xiang; Wang, Zicheng; Shangguan, Lingfei; Liu, Tianhua; Chen, Chun; Liu, Zhongjie; Ge, Mengqing; Zhang, Chuan; Zheng, Ting; Fang, Jinggui
Abstract: Copper stress is one of the most severe heavy metal stresses in plants. Grapevine has a relatively higher copper tolerance than other fruit crops. However, there are no reports regarding the tolerance mechanisms of the 'Shine Muscat' ('SM') grape to a low degree of excess copper stress (Low-ECS). Based on the physiological indicators and multi-omics (transcriptome, proteome, metabolome, and microRNAome) data, 8 h (h) after copper treatment was the most severe stress time point. Nonetheless, copper stress was alleviated 64 h after treatment. Cu ion transportation, photosynthesis pathway, antioxidant system, hormone metabolism, and autophagy were the primary response systems in 'SM' grapevine under Low-ECS. Numerous genes and proteins, such as HMA5, ABC transporters, PMM, GME, DHAR, MDHAR, ARGs, and ARPs, played essential roles in the 'SM' grapevine's response to Low-ECS. This work was carried out to gain insights into the multi-omics responses of 'SM' grapevine to Low-ECS. This study provides genetic and agronomic information that will guide better vinery management and breeding copper-resistant grape cultivars. Graphical abstract: Image 1 Highlights: Response network of grapevine leaves to Low-ECS were constructed via multi-omics. Chelation, segregation and efflux of copper were enhanced in leaves under Low-ECS. Antioxidant systems and hormone metabolism were induced to alleviate copper stress. Low-ECS enhanced ARGs and ARPs expressions and autophagosome formation. Abstract : The joint analysis of multi omics and physiological indexes indicated that grapevines mainly responded to Low-ECS by regulating copper transport, antioxidant pathway, hormone metabolism, and autophagy.